PEMANFAATAN LIMBAH IKAN SEBAGAI SUMBER ALTERNATIF PRODUKSI GELATIN, SEBUAH TINJAUAN LITERATUR SINGKAT - Pakalla, Jelin Tiku; ., Fetriyuna; Utoro, Panggulu Ahmad Ramdhani (Universitas Muhammadiyah Semarang, 2024)
Gelatin is a protein derived from the breakdown of collagen found in animals. It has diverse applications across industries such as pharmaceuticals, cosmetics, and especially the food industry. Fish waste, comprising skin, bones, and fins, represents a potential source for gelatin production. Hence, this article outlines advancements in utilizing fish waste for the gelatin production. The methodology involves a comprehensive review of scientific journals that focus on fish waste as the raw material for gelatin production. Findings from various studies indicate that waste from the skin and bones of different fish species, including barramundi, tilapia, red snapper, and tuna, can be utilized as sources of gelatin. Various extraction methods, such as enzymatic, acidic, and alkaline, result in diverse yield outcomes. The properties of the produced gelatin, including viscosity and gel strength, also exhibit variations based on the extraction methods employed and the type of fish waste utilized. Gelatin production from fish waste, especially skin and bones, has the potential to reduce environmental pollution and enhance the added value of fisheries in Indonesia, an archipelagic nation with a high fisheries production.